2023
DOI: 10.1111/den.14492
|View full text |Cite
|
Sign up to set email alerts
|

Risk and prognostic factors of invasive gastric cancer detection during surveillance endoscopy: Multi‐institutional cross‐sectional study

Abstract: Objectives Esophagogastroduodenoscopy (EGD) is important for the detection of curable gastric cancer (GC). However, there are no appropriate surveillance data during routine endoscopic inspections. This study aimed to clarify the risk factors of pT1b or deeper GC detection during surveillance endoscopy. Methods This was a retrospective, multicenter, cross‐sectional study conducted in 15 Japanese hospitals. We retrospectively analyzed patients with GC who had previously undergone surveillance endoscopy at each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 41 publications
(75 reference statements)
2
13
0
Order By: Relevance
“…reported that more than 95% of patients with metachronous gastric cancers could be treated by curative endoscopic resection, even if the interval between surveillance endoscopies was 1.0 year. Conversely, Yasuda et al 1 . reported that the proportion of T1b or deeper gastric cancers increased with increasing surveillance intervals in the medium‐risk group.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…reported that more than 95% of patients with metachronous gastric cancers could be treated by curative endoscopic resection, even if the interval between surveillance endoscopies was 1.0 year. Conversely, Yasuda et al 1 . reported that the proportion of T1b or deeper gastric cancers increased with increasing surveillance intervals in the medium‐risk group.…”
mentioning
confidence: 94%
“…The risk of gastric cancer was 1.7 (95% confidence interval [CI] 0.8–19.2) for moderate atrophy and 4.9 (95% CI 2.8–19.2) for severe atrophy when no to mild atrophy was set as 1 5 . In the cohort of Yasuda et al ., 1 90% of patients had open‐type atrophy, who may have had a relatively high risk of gastric cancer. Based on their results, a surveillance interval of ≤1.5 years may be recommended for those with severe atrophy to reduce the risk of surgical resection for gastric cancer 1 .…”
mentioning
confidence: 96%
See 3 more Smart Citations